A Multipoint Felled-Tree Validation of Height–Age Modeled Growth Rates. Issue 3 (6th February 2020) - Hemingway, Halli; Kimsey, Mark
Abstract: Accurate measures of forest site productivity are essential for forest-management planning. The most common measure of site productivity is breast height–age site index (BHASI)—the expected height at a reference age. Error from including early growth in productivity estimates and limited applicability of any one BHASI model warrant development of alternative methods. Exploring alternatives may only be necessary if regional BHASI models are not accurately predicting growth rates. We compared modeled height growth rates for Rocky Mountain Douglas-fir ( Pseudotsuga menziesii var. glauca ) to felled-tree measurements to evaluate relative performance of a regional BHASI model. An orthogonal sampling design ensured samples were collected across a range of site factors known to influence Douglas-fir growth rates. Growth rates for each 10 m section were calculated and compared to BHASI modeled growth rates. The regional BHASI model underpredicted growth rates from breast height to 30 m. Observed growth rates from 10 to 30 m accounted for the majority of underprediction relative to BHASI modeled growth rates. An alternative multipoint method of defining site productivity is described. More research comparing BHASI and alternative methods is needed, given the growth rate error associated with one-point site productivity assessment.